Recent progress on graphene-based materials for electromagnetic interference shielding applications - QIAN Wei; HE Da-ping; LI Bao-wen (Cailiao gongcheng, 2020)
The rise of the era of 5G wireless technology and development of flexible electronic devices have highlighted the key role of electromagnetic shielding materials for national defense and civil use. As a new carbon material, graphene has a unique two-dimensional structure showing excellent physical and chemical properties, which endows graphene-based materials light weight, good flexibility, high corrosion resistance and high electromagnetic shielding effectiveness. The shielding principle and the preparation method of graphene-based material were introduced in this review, and the latest advances on the electromagnetic shielding material were summarized, including pure graphene and graphene-based composite material. In addition, prospects for the future development of new graphene-based electromagnetic shielding materials were discussed.